Avanços, recuos, acertos e erros: Uma análise da resposta da política econômica brasileira à crise financeira internacional - Victor Leonardo de Araujo; Denise Lobato Gentil (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper aims to show that the fiscal and monetary counter-cyclical actions implemented by Brazilian government after the financial crisis were frugal: the monetary policy was late and slowly slackened and the fiscal policy sustain a primary surplus budget, in the opposite direction of much important economies around the world. Besides, foreign sector played an important role - commonly disregarded by most economists: the paper will show that foreign demand was an important channel to permit the economic's recovery and the international level of liquidity's recovery, for his part, allowed a sharp cambial crisis retrieval.
Keywords: G01; N15; 330; Wirtschaftspolitik; Geldpolitik; Finanzpolitik; Finanzkrise; Wirkungsanalyse; Brasilien